2006
DOI: 10.1258/096914106777589551
|View full text |Cite
|
Sign up to set email alerts
|

Cervical screening in 20–24-year olds

Abstract: The incidence of cervical cancer in young women has halved since the introduction of the Welsh-organized call-recall cervical screening programme. In Wales we recommend that women continue to be invited for cervical screening from 20 years of age. This will provide the information required to compare the incidence and stage at diagnosis of cervical cancer in young women invited for first time cervical screening at different ages across the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
1
15
0
2
Order By: Relevance
“…[644][645][646][647][648][649][650][651] Our search for new and pertinent studies identified four cohort studies relating to cervical cytology screening. [652][653][654][655] A related study 640 provided historical time trend mortality data related to cervical cancer screening programs. Finally, we identified one additional study reporting on the adverse events from human papillomavirus (HPV) vaccination in Australia 656 and one meta-analysis reporting adverse pregnancy outcomes associated with treatment of cervical dysplasia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[644][645][646][647][648][649][650][651] Our search for new and pertinent studies identified four cohort studies relating to cervical cytology screening. [652][653][654][655] A related study 640 provided historical time trend mortality data related to cervical cancer screening programs. Finally, we identified one additional study reporting on the adverse events from human papillomavirus (HPV) vaccination in Australia 656 and one meta-analysis reporting adverse pregnancy outcomes associated with treatment of cervical dysplasia.…”
Section: Resultsmentioning
confidence: 99%
“…644,645 The screening programs used invitation and reminder letters and practitioner incentives to increase screening rates from 61% to 83% of the population. Data from Rieck and coworkers 654 showed a reduction in cervical cancer (relative risk 0.48, 95% CI 0.23-0.98) (Table 21B). Adverse effects resulting from referral for colposcopy include anxiety about pain and discomfort.…”
mentioning
confidence: 91%
“…While some studies in developed countries recommend screening from age 20, others have confirmed cervical screening in women aged 20-34 is less effective than in older women (Rieck et al, 2006;Sasieni et al, 2009). Controversy is founded mainly on the anxiety of an abnormal test, unnecessary treatment to low grade lesions that might regress spontaneously, and on reports that have associated preterm delivery on pregnancies after treatment of lesions (Kyrgiou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This should be compared with a coverage rate of around 50% in the same age group. 1 These data show that women with cancer diagnosed at ages 20-24 are far more likely to have been screened than the general population (PE0.002). Indeed the data are interpretable only if a proportion of the eight screen-detected cancers would not have been diagnosed until age 25 (or older) in the absence of screening.…”
Section: Cases From Walesmentioning
confidence: 87%